The Effect of Azotobacter Strains on the Seed Germination Capacity of Wheat Varieties - o‘g‘li, Xabibullayev Abdulazizxon Omonillo; qizi, Xojiahmedova Gulira’no Saidabbos (American Journal of Biology and Natural Sciences, 2025)
This paper examines the influence of the Azotobacter strain on wheat growth; its impact on the biometric parameters of the agricultural crop (wheat) is determined. The selection of active strains isolated from the surface of winter wheat is studied, and their morphological, cultural, physiological and biochemical properties are analyzed. Particular attention is paid to the influence of Azotobacter on wheat growth and its impact on the biometric parameters of this crop.